Consultation Liaison Psychiatry: A Study at GMC (Journal of Psychiatrists' Association of Nepal, 2019)
Introduction: Consultation Liaison Psychiatry is the fusion of Psychiatry and general medicine. The presence of mental disorders in physically ill people is often associated with poor medication compliance, slower or incomplete recovery, poor participation in the rehabilitation program, increased mortality and the high psychiatric comorbidity to other medical disorders in hospitalized patients significantly increases their length of hospital stay. Therefore, mental health professionals have important role to provide holistic care to people with various physical illnesses. Material and Method: This is a hospital- based, cross- sectional, descriptive study conducted for the period of six months, from 1st Baisakh, 2076 (14th April, 2019) to 30th Asoj, 2076 (17th October, 2019) at the department of Psychiatry at Gandaki Medical College, Pokhara, Nepal. This study was conducted to diagnose the various psychiatric disorders among the in-patients suffering from other physical illness, which were referred from other medical specialties. The psychiatric evaluation and the diagnosis were made by the consultant psychiatrists. Results: The total number of cases enrolled were163, out of which male were 96 (58.8%) and female were 67 (41.2%) in numbers. The age of the patients ranged from 6 years to 90 years with the mean age of 41.17 ± 18.57 years. Majority of the in- patient cases referred for psychiatric assessment were from the Internal medicine (42.3%), followed by ICU (23.3%), Surgery (12.8%), Orthopedics (9.8%) and Gynecology and Obstetrics (7.3%) specialty. Among the in- patient referral cases, the most common psychiatric diagnosis was substance dependence syndrome (39.2%), followed by anxiety disorder (17.1%), delirium due to general medical condition (12.2%), depression (6.7%), seizure disorder (6.7%) and intentional self harm (5.5%). Conclusion: Under Consultation Liaison Psychiatry, the most common diagnoses to look for are the substance dependence syndrome, anxiety disorder, delirium, depression, seizure disorder, self harm etc.